Screen more, sell later: Screening and dynamic signaling in the mortgage market - Manuel Adelino; Bin Wei; Feng Zhao (Federal Reserve Bank of Atlanta, 2025)
In dynamic models of asset markets with asymmetric information and endogenous screening, the anticipation of signaling through delayed sales incentivizes originators to exert greater effort ex ante. A central prediction in those models is a positive relationship between screening effort and the delay of sale. We test this theoretical prediction using the mortgage market as a laboratory, with processing time serving as a measure of screening effort. In line with the theory, mortgage processing time and the delay of sale after origination are strongly positively related in the data. Both processing time and delay of sale are negatively related to conditional mortgage default, even though mortgages with higher ex ante credit risk are processed slower. This highlights the contrast between observable and unobservable risk and indicates that more screening effort leads to unobservably higher-quality loans that are also sold with a longer delay.
Keywords: G01; G21; G23; G32; R30; 330; processing time; screening; signaling; time to sale; securitization; mortgage loans; lending standards